THE ROLE OF UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT (USAID) IN NIGERIAN POLITICAL DEVELOPMENT SINCE THE FIRST ELECTION IN 1999 - 2011 - Muthmainnah (HI 15 UMY 246, 2015)
*246 Development for developing countries cannot be separated with the assessment of other actors outside the country. The role of other actors such as States to assist and influence the development in developing countries by giving money and programs. Some research attempt the bad effects of international assessment which means that the money they can provide can create the development worse due of various types of loan. There is no much research about the role of United States Agency for International Development (USAID) towards the development in developing world. This agency actually is an independent federal government agency of United States.